Representasi Makna Ideologis Kisah Ashab al-Kahf: Analisis Semiotika Roland Barthes Dalam Surah Al-Kahf - Hidayat, Wildan (Jurusan Tafsir Hadis Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2018)
The Qur’an which brings many messages of religion, moral and humanity sometimes gives the representation of messages that will be delivered. In many chapters of the Qur’an, Allah has given beautifully messages through the stories. The messages that will be delivered through the stories are the representation of religion purposed as the one of mankind servitude parts that called by ulu al-albab and ulu al-absar. In this context, the content of the message in the story of ashab al-kahf has an important message for human (ummah). The approach from language and semiotics aspects proposed by Roland Barthes has adequate mode of analysis for examining the ideological meaning within the text. It is all after the long process and mind mapping of reading theory that formulated by Roland Barthes, this paper argues that the concept of Roland Barthes will give the effects of ideological understanding and be able to represent the implicit meanings of ashab al-kahf story completely, at least close to intact, although the human not be able to interpret the meaning appropriately like the interpretation of the Glory (sahib al-nass). Through the mapping concept of Roland Barthes semiotics’ theory, the systemic interpretation and understanding of the religion purpose in proving the unity story in a chapter (surah) will be compiled.